Aplikasi Berbasis Android Dalam Meningkatkan Kognitif Anak Usia Dini - Desy Ayuningrum; Nur Afif (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
Early childhood cognitive formation is formed more quickly in the first four years of life in the golden age. The phenomenon of android-based application media in the digital age has been widely used as a means to optimize children’s cognitive development by some parents. The purpose of this study was to determine the role of android based application media in improving cognitive development in children. The method used in observasion is qualitative. As for the data collection techniques in the study are interview and observasions to five parens of android-based application usersas a means of stimulation to optimize children’s development in lampung. The result of the study illustrate that there is an increase in cognitive development in children. This it can be concluded that the android-based application media in the form of educational games and youtube kids can be used as a means to optimize cognitive development in early childhood.